Evaluating the effect of historical development on urban soils using microartifacts and geochemical indices - Konstantinova, Elizaveta Yu; Novoselov, Andrey; Konstantinov, Alexandr O.; Minkina, Tatiana; Sushkova, Svetlana; Loiko, Sergey V. (Environmental geochemistry and health)
The proposed research is devoted to the effects of the urbanization on the soil cover through the assessment of common organic and inorganic pollutants as well as anthropogenic microartifacts (MAs) over 20 sites characterizing different land use areas within the city of Tyumen, Russia. The analytical methods included measurements of physical-chemical properties of soils (total organic carbon content, pH, and texture), the total concentrations of potentially toxic elements (V, Cr, Co, Ni, Cu, Zn, As, Sr, and Pb) using X-ray fluorescence analysis, and the concentrations of 12 priority polycyclic aromatic hydrocarbons using high-performance liquid chromatography, and the evaluation of the composition of anthropogenic MAs assemblies by optical microscopy. The results of the study showed that the soils of all studied sites within the industrial areas were characterized by a high level of combined pollution with elements and compounds. For other sites, the duration of urbanization was the strongest factor that influenced the levels of pollution. The sites with the highest pollution levels were also characterized by the highest proportion and diversity of MAs. In contrast to the urban soils of the cities in North America and Western Europe, anthropogenic MAs associated with the use of coal (ash, slag, and silicon spheres) were present, but to a far lesser extent. Apparently, this is due to the fairly late development and intensive growth of Tyumen in the second half of the twentieth century, as well as the use of natural gas and fuel oil. At the same time, MAs associated with construction and domestic debris prevailed both in the soils of demolition sites and residential areas, which indirectly indicates the rapid and chaotic nature of urbanization, characteristic of Tyumen.